2006
DOI: 10.4172/plastic-surgery.1000490
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of finger flexor pulley injury in rock climbers: A systematic review

Abstract: BACKGROUND: Closed injury to the finger flexor pulley system is found frequently in rock climbers. There are no evidence-based published guidelines on the diagnosis and treatment of these injuries. OBJECTIVES: The present systematic review was undertaken to answer the following questions: what are the most commonly recommended diagnostic criteria for finger flexor pulley injury in rock climbers; and, based on the available evidence, what is the best diagnostic test for these injuries? METHODS: Four electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…A recent review article on the diagnosis of climbing-related finger injuries suggested that dynamic ultrasound was highly accurate for the diagnosis of finger pulley injuries. 22 Another review article on the imaging of climbing injuries also emphasized that ultrasound had distinct advantages for imaging finger injuries, including high spatial resolution and dynamic capabilities. 23 These features make ultrasound an important tool for imaging tendons, ligaments, nerves, and other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review article on the diagnosis of climbing-related finger injuries suggested that dynamic ultrasound was highly accurate for the diagnosis of finger pulley injuries. 22 Another review article on the imaging of climbing injuries also emphasized that ultrasound had distinct advantages for imaging finger injuries, including high spatial resolution and dynamic capabilities. 23 These features make ultrasound an important tool for imaging tendons, ligaments, nerves, and other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Acute tears of annular pulleys are frequently related to sport activities, specifically rock climbing, and mostly involve the middle and ring fingers . Patients present with pain and swelling over the affected pulley and may have a “pop” at the time of injury .…”
Section: Tendinous Instabilitymentioning
confidence: 99%
“…). At full text, 23 primary articles, 26 SR articles and six guidelines were included in the review.…”
Section: Resultsmentioning
confidence: 99%